1998
DOI: 10.1183/09031936.98.11061412
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease more than 40 years after a 5 year occupational exposure to talc

Abstract: A 62 yr old woman was initially diagnosed with sarcoidosis until a thoracoscopic biopsy revealed the presence of numerous birefringent particles in fibrotic areas of the centrilobular lung zones. These particles were examined by electron microscopy and X-ray spectrometry and characterized as impure talc. Further inquiry into her occupational history revealed that she had worked from the age of 14-18 yrs in a factory making rubber hoses, where she had had an intense exposure to talc. There was no evidence of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
1
17
0
3
Order By: Relevance
“…Seasonal clustering of sarcoidosis in the months of June and July [27], change of prevalence over climate zones [9], time and space clusters [28,29], an increased incidence in health workers [30], an association of environmental exposure with sarcoidosis [31] or specific sarcoidosis phenotypes [32] and the transmission or recurrence of sarcoidosis by or in transplants [33,34] have been observed and support the hypothesis of transmissible animate sarcoidosis-inducing agents. Numerous case series, case reports, and epidemiologic studies demonstrated an association between sarcoidosis with uptake of silica [31], talc [35,36], man-made fibres [37] or other inanimate agents [38,39] by inhalation or ingestion at work place [28,32,[40][41][42], at home [32,43], from the environment [32] or as components of pharmaceutical products [44]. Exposure to crystalline silica is associated with a number of chronic pulmonary and extrapulmonary disorders next to silicosis but in contrast to the above mentioned study from Iceland [31] an association with sarcoidosis could not be identified using data from a occupational mortality surveillance program [45].…”
Section: Etiologymentioning
confidence: 99%
“…Seasonal clustering of sarcoidosis in the months of June and July [27], change of prevalence over climate zones [9], time and space clusters [28,29], an increased incidence in health workers [30], an association of environmental exposure with sarcoidosis [31] or specific sarcoidosis phenotypes [32] and the transmission or recurrence of sarcoidosis by or in transplants [33,34] have been observed and support the hypothesis of transmissible animate sarcoidosis-inducing agents. Numerous case series, case reports, and epidemiologic studies demonstrated an association between sarcoidosis with uptake of silica [31], talc [35,36], man-made fibres [37] or other inanimate agents [38,39] by inhalation or ingestion at work place [28,32,[40][41][42], at home [32,43], from the environment [32] or as components of pharmaceutical products [44]. Exposure to crystalline silica is associated with a number of chronic pulmonary and extrapulmonary disorders next to silicosis but in contrast to the above mentioned study from Iceland [31] an association with sarcoidosis could not be identified using data from a occupational mortality surveillance program [45].…”
Section: Etiologymentioning
confidence: 99%
“…Other case reports have revealed interesting exposure histories. To name some, a brief 5 year occupational exposure to pure talc resulted in symptomatic disease four decades later2 or cases of patients presenting with progressive restrictive respiratory symptoms who on probing reported their chronic daily routine of cosmetic talcum powder dusting of their bodies since many years 3 9. In this regard, the case we have reported shows a fascinating exposure history.…”
Section: Discussionmentioning
confidence: 80%
“…Occupational exposure to pure talc during its production or industrial use remains to be a well-known aetiological factor in causing pulmonary talcosis, symptoms of which may occur after several years following exposure 1 2. Other forms of pulmonary pneumoconiosis involve exposure to impure varieties of talc containing asbestiform fibres and silica affecting mainly miners and intravenous drug misusers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies confirm an association between cumulative exposure to talc and respiratory disease. However, even a relatively short, intense exposure to talc can result in diffuse pulmonary disease, with a latency period of more than 40 years (Gysbrechts et al 1998). According to Feigin (1986) and Rom (1998), talc-induced pulmonary disease has four distinct manifestations, the first of which is talco-silicosis, which is similar to silicosis.…”
Section: Discussionmentioning
confidence: 99%